Peningkatan Hasil Belajar Tingkat Tinggi Mata Pelajaran Bahasa Inggris Materi Analytical Exposition Melalui Pembelajaran Covid-19 Metode Blended Learning Pada Kelas XI IPS 6 SMAN 1 Kecamatan Harau Semester Ganjil Tahun Pelajaran 2021/2022 - Septi Efa (Departement of Mathematics Education, 2022)
The purpose of this study is to describe the use of blended learning Covid-19 learning to improve high-level learning outcomes of students in English subjects in Class XI IPS 6 SMAN 1 Harau District. This type of research is Classroom Action Research. The research was carried out based on classroom action research steps with two cycles starting from the planning, implementation, observation and reflection stages. Research data in the form of test results, learning observations, field notes, and documentation of each learning improvement action. The source of research data is the process of learning activities. Data were obtained from the research subjects, namely teachers and students of class XI IPS 6, totaling 37 people, which was held from July to July. October 2021. The results of the research data analysis show that the use of a scientific approach to the blended learning method can improve the ability of teachers to prepare high-level questions. This is evidenced by the acquisition of a score of 64.58 in the spracycle, increased to 72.91 in the first cycle, and increased to 89.58 in the second cycle. Furthermore, the results of the study of descriptions also experienced an increase, namely 64.10 in the pre-cycle, increasing to 76.92 in the first cycle of activities, and increasing to 87.71 in the second cycle. Furthermore, the learning outcomes of high-level thinking students in the knowledge aspect have increased, namely 68.07 in pre-cycle activities, increasing to 79.35 in the first cycle, increasing again to 81.75 in the second cycle with a large increase of 13.68. The learning outcomes of skills aspect obtained an average of 68.45 in the pre-cycle, increasing to 77.89 in the first cycle and increasing again to 80.89 in the second cycle with a large increase of 11.44. Based on the results of this study, the conclusions of research using a scientific approach to the blended learning method in English subjects need to be applied and developed in order to improve the quality of education.